2015
DOI: 10.1093/cvr/cvv247
|View full text |Cite
|
Sign up to set email alerts
|

Ranolazine antagonizes catecholamine-induced dysfunction in isolated cardiomyocytes, but lacks long-term therapeutic effectsin vivoin a mouse model of hypertrophic cardiomyopathy

Abstract: Ranolazine improved tolerance to high workload in mouse HCM cardiomyocytes, not by blocking late Na(+) current, but by antagonizing β-adrenergic stimulation and slightly desensitizing myofilaments to Ca(2+). This effect did not translate in therapeutic efficacy in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 72 publications
8
61
0
1
Order By: Relevance
“…Ranolazine has a significant β-blocking effect when the plasma concentration is >13 μmol/L, 47 much higher than the clinically relevant concentration range (from 2 to 5 μmol/L). Indeed, Flenner et al 46 reached very high plasma ranolazine concentrations in their treated mice (>20 μmol/L), so a β-blocking effect observed with their protocol is expected, but scarcely clinically relevant. In our ranolazine-treated male mice, plasma ranolazine concentration ranged from 2.5 to 5.5 μmol/L (average 4 μmol/L).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Ranolazine has a significant β-blocking effect when the plasma concentration is >13 μmol/L, 47 much higher than the clinically relevant concentration range (from 2 to 5 μmol/L). Indeed, Flenner et al 46 reached very high plasma ranolazine concentrations in their treated mice (>20 μmol/L), so a β-blocking effect observed with their protocol is expected, but scarcely clinically relevant. In our ranolazine-treated male mice, plasma ranolazine concentration ranged from 2.5 to 5.5 μmol/L (average 4 μmol/L).…”
Section: Discussionmentioning
confidence: 97%
“…In human cardiomyocytes from adult patients with HCM, however, we previously showed that similar electric abnormalities (including increased I NaL ) are also present in cardiomyocytes from patients carrying MyBPC mutations, 10 and the benefits of acute ranolazine administration seemed independent from the presence of a specific mutation. The cardiac pathological phenotype of the MyBPC mouse model in the work by Flenner et al 46 was rather mild, with slight diastolic dysfunction, minimal LV hypertrophy, and little cellular abnormalities, 33 and provided a lesser approximation of advanced human disease as observed in patient samples, 10 as compared with the R92Q model. Moreover, Flenner et al started treatment in young adult mice of 2 months of age when disease phenotype was already fully expressed, 33 while we initiated treatment right after birth, before HCM phenotypic expression.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations